Contemporary Case Studies on Fashion Production, Marketing and Operations (Springer Series in Fashion Business,, 2018)
This book adopts a case study based research approach to examine the contemporary issues in the fashion industry. It documents real-world practices in fashion business from production, marketing to operations. Founded on an extensive review of literature, these case studies discuss the challenges that are pertinent to the current business environment in this important industry, provide benchmarks and generate insights to practitioners as well as suggest future directions to researchers. The book serves as a nexus of the theories and the industrial practices that advances knowledge for both the academia and the private sector in fashion business.